Beam transport line with scaling fixed field alternating gradient type magnets - Shinji Machida; Richard Fenning (Physical Review Special Topics. Accelerators and Beams, 2010)
A scaling fixed field alternating gradient (FFAG) accelerator provides large momentum acceptance despite the fact that magnetic guiding fields are constant in time. Optical functions are identical over the large momentum range as well. We have designed a straight beam transport line (BTL) using a scaling FFAG type magnet which has a field profile of y^{k}, where y is the horizontal coordinate and k is the magnetic field index. This FFAG-BTL has very large momentum acceptance and optical functions that, practically speaking, do not depend on momentum. We also designed a dispersion suppressor at the end of the line by combining unit cells with a different field index k so that the momentum dependence of orbit location should be eliminated at the exit. An obvious application of this design is the BTL after an FFAG accelerator to a patient in a hadron therapy facility or to a target in general. This could be an alternative to the conventional BTL with solenoids or quadrupoles because of the strong focusing nature of a quadrupole and the large momentum acceptance like a solenoid.